2023
DOI: 10.1038/s41598-023-27947-z
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of patients who died in the emergency departments and need of end-of-life care in Korea from 2016 to 2019

Abstract: The need of palliative care at the end-of-life in the emergency departments (ED) is growing. The study aims to investigate the epidemiology of patients who died during care in ED using nationwide database, and to estimate the need for palliative care in the ED. A retrospective observational study was conducted using the National Emergency Department Information System (NEDIS) database. Patients who died during ED care between 2016 and 2019 were included. Palliative care-eligible disease was defined as cancer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In our study, based on the palliative care encounter indicator, nearly half of older patients appeared to present with an understanding that they might be at their end of life. Based on other studies, a palliative approach would be appropriate for about one-quarter to one-half of older patients [ 15–17 ]. Despite guidelines and recommended geriatric ED model designs [ 30–32 ], few EDs are set up to manage the special needs of the older person [ 33 , 34 ], regardless of whether they present at end of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, based on the palliative care encounter indicator, nearly half of older patients appeared to present with an understanding that they might be at their end of life. Based on other studies, a palliative approach would be appropriate for about one-quarter to one-half of older patients [ 15–17 ]. Despite guidelines and recommended geriatric ED model designs [ 30–32 ], few EDs are set up to manage the special needs of the older person [ 33 , 34 ], regardless of whether they present at end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Few other estimates of the incidence of death in ED or shortly thereafter exist. One population-based Korean study reports an ED death rate of 0.3% (all ages), and that approximately one-quarter of patients who died in ED would have been considered appropriate for palliative care based on pre-existing health conditions [ 15 ]. A second single-site study from Singapore found that more than half of older persons who died in ED were chronically unwell and more likely to benefit from palliative care [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that 40.7% of PC patients coming to ED died in a hospital [9]. The prevalence of ED visits among PC patients has been reported to range from 13.2% to 25% [10,11]. However, it is important to note that the availability of data relating to this subject is currently limited [12].…”
Section: Discussionmentioning
confidence: 99%
“…As the frequency of advanced diseases becomes more common, there is a corresponding rise in ED visits for individuals with chronic illnesses. For example, in the period 2016–2019 in Korea, only 10% of deaths that occurred in the ED were attributed to injuries, while a staggering 90% of the deaths were linked to various diseases, and more than half of elderly patients who passed away in the ED had significant chronic illnesses [ 1 ]. Drawing from yet another extensive cohort of over a hundred million ED patients, the study’s authors reached the conclusion that there is a need to identify patients for whom end-of-life care is either necessary or preferred, and to ensure they are equipped to receive this care at an excellent standard (highlighting older patients who are more likely to be White, male, not Hispanic, and possess a higher Charlson Comorbidity Index) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%